TRANSFORMING SUFISM INTO DIGITAL MEDIA - Ziaulhaq Hidayat (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2022)
This article seeks to examine the rise of tarekat (Sufi order) in the context of the digital public sphere with a special attention to the Eshaykh website. As this article argues, the Eshaykh website represents an adaptation of conventional groups of tarekat combined with information technology. However, this digital adoption raises a new problem, especially related to the differences in terms of access between digital tarekat and conventional tarekat. This article—using a virtual ethnographic approach—focuses on the Eshaykh website by the Tarekat Naqsyabandiyah Haqqaniyah (TNH) as the primary source. The website provides all information about the tarekat, both the doctrine and the wirid, which are presented online. There is also an element of the simplification of orthodoxy which has so far been strictly guarded by conventional tarekat, but the rise of the Eshaykh website in the digital public sphere is offering tarekat practices that are easily accessible and reach all levels of society.